The medicalization of suffering and the overdiagnosis of depression - Degrave, Aline; Silva, Paulo Roberto Fagundes da (Saúde em debate (Londrina, Brazil), 2025)
ABSTRACT The use of diagnostic manuals and the statistical effort to catalog mental illnesses and disorders have been the subject of reflection for various health and social science researchers. Although there is an effort to universalize and transculturalise psychodiagnostic categories, there is also a need to abandon an exclusively biological model, giving way to a cultural understanding of the manifestations of psychological suffering. Depression has been treated as an epidemic by a variety of international health actors, leading to an exponential increase in pharmacological prescriptions and significant costs for health systems. Contrary to this warning, a substantial body of theory suggests a global trend towards the medicalization of human suffering in the experience of depression, resulting in overdiagnosis of the condition that has adverse consequences for users of health services. Based on an ethical, methodological, and scientific concern to promote critical science and good clinical practice, this essay seeks to discuss the factors that contribute to shaping the process of medicalizing depression, how the diagnosed individual canbe decentralized from their experience, and how the processes of formulating a diagnosis and clinical intervention are influenced by theoretical, economic, social, political and circumstantial factors, leading to individualization of social and contextual problems. RESUMO O uso de manuais diagnósticos e o esforço estatístico para a catalogação de transtornos mentais têm sido tema de reflexão para gerações de profissionais e pesquisadores. Embora haja um esforço para universalizar e transculturalizar categorias psicodiagnósticas, também há necessidade de abandonar um modelo exclusivamente biológico, dando espaço para uma compreensão cultural das manifestações do sofrimento psíquico. A depressão vem sendo tratada como uma epidemia por variados atores internacionais da saúde, levando a um aumento exponencial de prescrições farmacológicas e a custos significativos para os sistemas de saúde. Contrariando esse alerta, um conjunto teórico substancial sugere uma tendência global de medicalização do sofrimento humano na experiência da depressão, resultando em um sobrediagnóstico do quadro que traz consequências adversas para os usuários dos serviços de saúde. A partir de uma preocupação ética, metodológica e científica para promover uma ciência crítica e uma boa prática clínica, este ensaio busca discutir os fatores que concorrem na configuração do processo de medicalização da depressão, como o indivíduo diagnosticado pode ser descentralizado de sua experiência e como os processos de formulação de diagnóstico e intervenção clínica são influenciados por fatores teóricos, econômicos, sociais, políticos e circunstanciais, levando a uma individualização de problemas sociais e contextuais.